Clinical features, outcomes and treatment in children with drug induced Stevens-Johnson syndrome and toxic epidermal necrolysis - Liotti, Lucia; Caimmi, Silvia; Bottau, Paolo; Bernardini, Roberto; Cardinale, Fabio; Saretta, Francesca; Mori, Francesca; Crisafulli, Giuseppe; Franceschini, Fabrizio; Caffarelli, Carlo (Acta Biomedica Atenei Parmensis, 2019)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN), which can be considered a late-onset allergic reaction, can cause serious long-term sequelae. SJS/TEN are considered a spectrum of life-threatening adverse drug reactions. They have the same clinical manifestations and the only difference is in the extent of epidermal detachment. These conditions are associated with high mortality, although incidence of SJS/TEN is rare in children. SJS/TEN is an adverse drug reaction influenced by genes that involve pharmacokinetics, pharmacodynamics and immune response. Infective agents are additional influencing factors. Anticonvulsants and antibiotics, and especially sulphonamides and non-steroidal anti-inflammatory drugs, are among the drugs that were predominantly suspected of triggering SJS/TEN. No evidence-based standardized treatment guidelines for SJS or TEN are currently available. The usual treatment is mainly founded on the withdrawal of the suspected causative agent and supportive therapy. In pediatric patients, the specific therapeutic strategies are controversial and comprise systemic corticosteroids and the use of intravenous immunoglobulin (IVIG). More recently, new therapeutic approaches have been used, such as immunosuppressive therapies, including cyclosporine and TNF-α inhibitors.